Students’ Perception of Learning English Using Google Classroom Media During The Covid-19 Pandemic - Reski Triana; Fajriani Fajriani; Ridwan Ridwan (Institut Agama Islam Negeri Palopo, 2022)
This study aims to find out how students' perceptions of learning English use google classroom media during the Covid-19 pandemic and to find out what are the inhibiting factors experienced by students d[1]uring the learning process of English using Google Classroom media.This type of research uses a qualitative approach, in data collection techniques the researcher uses the methods of observation, interviews, and documentation.Informants in this study were students of class XI. 1 TKJ and English teacher at SMK YPPP WONOMULYO.Based on the results of observations the conditions of the implementation of English language learning in the Pandemic Covid-19 are very different when the learning process carried out face-to-face where the teacher's English learning process no longer explains the material directly but the teacher uses the Google Classroom media as a forum to carry out the learning process for students then the interview process was carried out by researchers through Google Form.The results of the study stated that the majority of class XI students. 1 TKJ SMK YPPP WONOMULYO has a negative perception of online learning English. This is in accordance with the answers of students who said they preferred face-to-face learning because it was easier to understand and learning through Google Classroom experienced many obstacles, for example network connections were often bad or constrained by internet quotas. Then the students said the learning outcomes were unsatisfactory and less understood and unattractive. Then the inhibiting factors experienced by students are unstable networks, sometimes Google Classroom errors, inadequate quotas and lack of understanding of the material presented and lack of socializing with teachers and students.Â